2015
DOI: 10.18857/jkpt.2015.27.3.147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Abdominal Drawing-in Maneuver and the Abdominal Expansion Maneuver on Grip Strength, Balance and Pulmonary Function in Stroke Patients

Abstract: Purpose:The purpose was to determine whether the application of the abdominal drawing-in maneuver (ADIM) and abdominal expansion maneuver (AEM) to stroke patients would affects their trunk stability, balance, pulmonary function, and grip strength. Methods: The subjects were 36 stroke patients who were randomly and equally assigned to an ADIM group (n = 12), an AEM group (n= 12), and a control group (n= 12). The intervention was applied to each group three times per week, 30 minutes each time, for four weeks. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…If the navel extends in the caudal anterior direction, it may have the advantage of being able to increase the IAP, the simultaneous contraction of the diaphragm, and deep spinal stabilizer muscles. ADIM training was performed in the prone position using a pressure bio-feedback system, which has been commonly used to give stability to the pelvis and lower back area during movement of the upper and lower limbs [14]. We performed the ADIM training in the prone position with adults with instability that was reported of the thickened core muscle, the transverse abdominis, and obliqus abdominus interni.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…If the navel extends in the caudal anterior direction, it may have the advantage of being able to increase the IAP, the simultaneous contraction of the diaphragm, and deep spinal stabilizer muscles. ADIM training was performed in the prone position using a pressure bio-feedback system, which has been commonly used to give stability to the pelvis and lower back area during movement of the upper and lower limbs [14]. We performed the ADIM training in the prone position with adults with instability that was reported of the thickened core muscle, the transverse abdominis, and obliqus abdominus interni.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were instructed to keep breathing in this state and to keep the posture for 10 seconds. After repeating the AEM 10 times, a 3-minute break was given and an application of 3 sets of AEM for 15 minutes was administered in total [14].…”
Section: Aemmentioning
confidence: 99%
See 2 more Smart Citations
“…And found that the change of PEF (peak expiratory flow) in the ADIM (abdominal drawing-in maneuver) and AEM groups is larger compared with control group [12].…”
mentioning
confidence: 89%